Associations between persistent organic pollutants and risk of breast cancer metastasis. (November 2019) - Koual, Meriem; Cano-Sancho, German; Bats, Anne-Sophie; Tomkiewicz, Céline; Kaddouch-Amar, Yael; Douay-Hauser, Nathalie; Ngo, Charlotte; Bonsang, Hélène; Deloménie, Myriam; Lecuru, Fabrice; Le Bizec, Bruno; Marchand, Philippe; et al.
Abstract: Background: Breast cancer (BC) is a major public health concern with over 2 million new cases diagnosed and over 600, 000 deaths in 2018 in women worldwide. When distant metastases are present at diagnosis, the 5-year survival rate is only 26%. Recent studies have suggested that persistent organic pollutants (POPs) that accumulate in adipose tissue (AT) can influence tumor phenotype and stimulate cellular processes important for metastasis such as invasion. We, therefore, tested the hypothesis that POP exposure is associated with BC metastasis. Methods: We conducted an exploratory case-control study in which the concentrations of 49 POPs were measured in both AT and serum samples from BC patients, with or without lymph node metastasis, who underwent partial or total mastectomies, lymph node biopsies and sampling of the adipocytic tumor microenvironment. Adjusted, unconditional logistic models were used to study the associations between the POP concentrations and the risk of metastasis and other hallmarks of cancer aggressiveness. Results: 2.3.7.8-TCDD concentrations in AT are positively associated with the risk of metastasis in 43 patients who have BMIs equal or higher than 25 kg/m2 (odds ratio: 4.48 (1.32–20.71)). Furthermore, the concentrations of 2.3.7.8-TCDD and two coplanar PCBs (77&169) in AT also were positively associated with the risk of lymph node metastasis and the tumor size. Conclusion: Our study suggests that 2.3.7.8-TCDD and some PCBs contribute to the development of tumor metastasis and other hallmarks of cancer aggressiveness. While these results should be considered with caution, this is the first study to identify such potential risk factors. Larger longitudinal studies are necessary to confirm our results. Clinical Trial Protocol Record : 2013-A00663-42. Highlights: No observational studies have been conducted to evaluate the link between EDC and breast cancer metastasis. The concentrations of 49 POPs were measured in AT from breast cancer patients with or without lymph node metastasis. The concentrations of TCDD in AT are positively associated with the risk of metastasis in overweight patients. The concentrations of TCDD, PCB77 and PCB 169 in AT were positively associated with the tumor size.